Implementation of Behavioristic Theory in Learning Islamic Religious Education in Senior High School - Sabrina, Rifdah; Suprianto, Bibi; Rohman, Rohman; Fatimah, Fatimah; Piter, Alexy (Al-kayyis: Journal of Islamic Education, 2023)
Behavioristic learning theory is a learning theory that focuses on changes in students' behavior towards stimuli and responses, meaning that students are said to have learned if they have shown changes in their behavior. Morals are human behavior in everyday life that is inherent in a person. Therefore, behavioristic learning theory has a big influence in forming students with character and noble morals. Therefore, research needs to be carried out to identify how the implementation of behavioristic learning methods in Islamic religious education learning affects students' moral development. This research aims to identify the implications of behaviorist learning theory in Islamic Religious Education learning on the morals of students at the high school level. This research uses a qualitative method with a case study type (case study), data sources were taken from two informants through direct interviews with the informants using a set of interview protocols. All data was analyzed theoretically using software NVivo 12. The results of the research found three themes in the form of implementation of behavioristic learning theory in Islamic religious education learning regarding morals in high school. The three themes are learning based on environmental care, educators must be role models in educating students' morals, providing sanctions and rewards. The results of this research can be used as a reference in implementing behavioristic learning theory in Islamic religious education learning regarding the morals of students in high school. The results of this research can be used as initial data for researchers next in examining this problem in the context of different issues.